Dukkha e angústia: uma exploração a partir do budismo e da psicanálise sobre o sofrimento humano - Nascente, Heloísa Moschen de Paula (Universidade Federal de São Carlos, 2024)
This work aims to analyze the intersection between psychoanalysis and buddhism, two approaches that, despite their distinct origins, share common ideas in understanding human suffering and seeking strategies to deal with it. Initially, we will examine the buddhist perspective, focusing on the concept of dukkha. In the subsequent chapter, we delve into Freudian psychoanalysis, investigating how anxiety is conceptualized and its role in psychic dynamics. In the following, we will seek to promote a dialogue between these perspectives, focusing on the ideas of the Buddhist Sangha and the significance of the other for psychoanalysis. Finally, in the conclusion, we propose reflections on paths toward accepting human suffering. This work aims to enrich the academic discourse by fostering a dialogue between these two perspectives, providing insights into the understanding of suffering in human existence.
Dukkha and anxiety: an exploration of human suffering from Buddhism and psychoanalysis
Keywords: Budismo; Psicanálise; Sofrimento; Angústia; Dukkha; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS